A mycotoxin transporter (4D) from a library of deoxynivalenol-tolerant microorganisms. (March 2020) - Jimenez-Sanchez, Celia; Wilson, Nina; McMaster, Nicole; Gantulga, Dash; Freedman, Benjamin G.; Senger, Ryan; Schmale, David G.
Abstract: New strategies are needed to mitigate the mycotoxin deoxynivalenol (DON) in feed and food products. Microbial DNA fragments were generated from a library of DON-tolerant microorganisms. These fragments were screened in DON-sensitive yeast strains for their ability to modify or transport DON. Fragments were cloned into a PCR8/TOPO vector, and recombined into the yeast vector, pYES-DEST52. Resulting yeast transformants were screened in the presence of 100 ppm DON. Transformants that were able to grow in the presence of DON were plated on a selective medium, and the cloned microbial DNA fragments were sequenced. BLAST queries of one microbial DNA fragment (4D) showed a high degree of similarity to an ABC transporter. A series of screening and inhibition assays were conducted with a transport inhibitor (propanol), to test the hypothesis that 4D is a mycotoxin transporter. DON concentrations did not change for yeast transformants expressing 4D. The ability of yeast transformants expressing 4D to transport DON was inhibited by the addition of propanol. Moreover, yeast transformants expressing a known efflux pump (PDR5) showed similar trends in propanol transport inhibition compared to 4D. Future work should consider mycotoxin transporters such as 4D to the development of transgenic plants to limit DON accumulation in seeds. Highlights: Microbial DNA fragments were generated from a library of DON-tolerant microorganisms. Fragments were screened in DON-sensitive yeast strains for their ability to modify or transport DON. BLAST queries of one microbial fragment (4D) showed a high degree of similarity to an ABC transporter. Transformants expressing a known efflux pump (PDR5) showed similar trends in propanol transport inhibition compared to 4D. Future work should consider mycotoxin transporters such as 4D to the development of transgenic plants.